Self-Regulated Learning and Mathematical Anxiety in Relation to Critical Thinking Ability - Yani, Fitri; Miatun, Asih (Lectura : Jurnal Pendidikan, 2024)
Mathematics has a significant positive impact on the advancement of science and technology, as well as the development of information and communication technologies. The purpose of this research is to investigate the relationship between self-regulated learning and mathematical anxiety in relation to students’ critical thinking ability. This research was a quantitative analysis using a correlational method. This research’s population encompassed 252 high scholars of a senior high school in Jakarta. The sample was recruited using the cluster random sampling technique, comprised 155 students. This study used a critical thinking ability test, along with non-test instruments including self-regulated learning and mathematical anxiety questionnaires. Multiple linear regression tests were performed in data analysis techniques by calculating the coefficients of determination and conducting hypothesis tests using F and T tests. The coefficient of determination output revealed that critical thinking ability was influenced by self-regulated learning and mathematical anxiety by 25.3%. The hypothesis testing outcomes using the F-test denoted a simultaneous influence of self-regulated learning and mathematical anxiety on learners’ critical thinking ability. However, the partial hypothesis testing using the T-test indicated no relationship between students’ critical thinking ability and self-regulated learning. At last, the T-test revealed a negative relationship between students’ critical thinking ability and mathematical anxiety.